Pulsing Preservatives to Prolong Vase Life of Cut Rose Flowers in Bahir Dar, Northwestern Ethiopia - Zelalem, Selamawit; Alemayehu, Melkamu; Yeshiwas, Tadele (International Journal of Sustainable Agricultural Research, 2018)
The longevity of cut flowers including cut roses can be however prolonged using different pulsing preservatives where researches in this regard are lacking in the country. Keeping these bottlenecks of the sector in mind, this study was therefore initiated with objective to evaluate the effectiveness of different pulsing preservatives in prolonging vase life of cut rose varieties. The experiment was conducted at Tana Flora PLC in Bahir Dar, Ethiopia. As pulsing preservatives Al2(SO4)3)(250 mg-1), Ca(ClO)2 (66.7 mg-1), STS [Ag (S2O3)2] (0.5 ml-1), Sugar (20 g-1) and distilled water were used. The three rose varieties namely: Upper class, Athena and Moon walk were used. Healthy flower buds having uniform length and harvested early in the morning were put immediately in containers filled with the respective concentration of pulsing preservatives. Flasks with six rose flowers each were placed in pre-cooling room (8-10 OC) for about 2 hours. Finally, treated cuttings were transferred into experimental room with temperature of 22-250C and 75% relative humidity and arranged in Complete Randomized Design (CRD) with three replications. At this time, pulsing preservatives were replaced by distilled water. The analysis of variance revealed that most of parameters were highly significantly influenced by the main as well as interaction effects of pulsing preservative and varieties (P<0.0). Maximum water uptake (7.73 g/flower/day), transpiration loss (7.08 g/flower/day), flower fresh weight (21.77 g/flowers), flower head diameter (7.6 cm), and maximum flower vase life (23 days) were recorded in Athena variety pulsed with STS.